Intelligent Human Computer Interaction: 9th International Conference, IHCI 2017, Evry, France, December 11-13, 2017, Proceedings - Horain, Patrick; Achard, Catherine; Mallem, Malik (Information Systems and Applications, incl. Internet/Web, and HCI, 2017)
This book constitutes the thoroughly refereed proceedings of the 9th International Conference on Intelligent Human Computer Interaction, IHCI 2017, held in Evry, France, in December 2017. The 15 papers presented together with three invited papers were carefully reviewed and selected from 25 submissions. The conference is forum for the presentation of technological advances and research results at the crossroads of human-computer interaction, artificial intelligence, signal processing and computer vision. This book is open access under a CC BY license.